Systemowe ujęcie biosfery w etyce Edwarda Goldsmitha - Anita Ganowicz-Bączyk (Studia Ecologiae et Bioethicae)
Environmental ethics has been intensively developed since the 1970s and is promoted most of all by philosophers and philosophizing naturalists. Various attitudes have been adopted, differing deeply ontologically, anthropologically, and axiologically. In this article, the ethics of Edward Goldsmith are presented. Goldsmith understands the biosphere as a systemic whole, which should be treated with moral respect and responsibility by humankind. In the beginning, the notion of holism is defined and described against the background of biocentric and anthropocentric ethics. Next, the views that inspired Goldsmith’s theory are presented, i.e. A. Naess’ deep ecology, J. Lovelock and L. Margulis Gaia’s hypothesis, the views of E. Odum, W.B. Cannon and C.H. Waddington. Then the main points of biospheric ethics are presented. Finally, Goldsmith’s proposal of mental and civilizational shift is submitted. The biospheric morality, which is supported by religious norms, is explained. This type of morality should allow humankind to achieve the right way of development.